2000
DOI: 10.1038/sj.onc.1203415
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRAF2/GCK in melanoma sensitivity to UV-induced apoptosis

Abstract: Radiation resistance is a hallmark of human melanoma, and yet mechanisms underlying this resistance are not well understood. We recently established the role of ATF2 in this process, suggesting that stress kinases, which contribute to regulation of ATF2 stability and activity, play an important role in the acquisition of such resistance. Here we demonstrate that changes in the expression and respective activities of TRAF2/GCK occur during melanoma development and regulate its sensitivity to UV-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…Our previous studies have demonstrated the changes in TRAF2/GCK expression and activities during melanoma progression. Through the regulation of both p38 and JNK signaling TRAF2/GCK and their e ectors p38/JNK kinases and ATF2/c-Jun transcription factors were implicated in melanoma sensitivity to radiation (Ivanov et al, 2000;Ivanov and Ronai, 1999;Ronai et al, 1998). Data shown in the present study identi®es another layer of regulation, namely, the suppression of Fas expression upon p38 activation.…”
Section: Cell Linessupporting
confidence: 50%
See 1 more Smart Citation
“…Our previous studies have demonstrated the changes in TRAF2/GCK expression and activities during melanoma progression. Through the regulation of both p38 and JNK signaling TRAF2/GCK and their e ectors p38/JNK kinases and ATF2/c-Jun transcription factors were implicated in melanoma sensitivity to radiation (Ivanov et al, 2000;Ivanov and Ronai, 1999;Ronai et al, 1998). Data shown in the present study identi®es another layer of regulation, namely, the suppression of Fas expression upon p38 activation.…”
Section: Cell Linessupporting
confidence: 50%
“…This early-phase melanoma cell line exhibits low activity of JNK and NF-kB which were shown to be attributed to poor GCK expression (Ivanov et al, 2000). The WM1552 cells possess poor NF-kB and Fas activities as re¯ected in the analysis of the respective promoters (not shown).…”
Section: Low Nf-kb Activity and Poor Fas Expression Coincides With Himentioning
confidence: 92%
“…Among the GCK subfamily I kinases, we also observed NFB activation by the closest HPK1 homologue GCKR/KHS, whereas the more distantly related GCK caused only moderate NFB activation, and GLK failed to elicit any activity in COS1 cells. NFB activation by GCK-related kinases may be highly cell type-dependent as GCK and GCKR/KHS failed to affect NFB in HEK293 cells (11), whereas in melanoma cells GCK activated NFB moderately (42).…”
Section: Discussionmentioning
confidence: 99%
“…This activity markedly increases during tumor progression (Rutberg et al, 1994;Ivanov et al, 2000a). Members of the AP-1 family, including c-Jun, have been implicated in controlling the balance between cell survival and death (Karin and Lin, 2002;Shaulian and Karin, 2002).…”
Section: Rasmentioning
confidence: 99%